2013
DOI: 10.1016/j.tetlet.2013.03.120
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic assembly of cytochalasin backbone

Abstract: Leave this area blank for abstract info.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…Consistent with this hypothesis is the observation that the ACE1 terminal-domain has an intact conserved NADPH binding motif (GXSXXG) and the catalytic triad Ser-Tyr-Lys more closely resembles ‘ reducing ’ R-domains than DKC cyclising domains (see ESI † ). 24 Qiao et al predicted a reductive release for ccsA , the PKS-NRPS gene involved in cytochalasin K 4 biosynthesis in Aspergillus clavatus , 27 based on the same rationale, and the co-expression of ccsA with ccsC by Oikawa and co-workers led to the production of the amide 17 , 14 also at the alcohol oxidation state.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis is the observation that the ACE1 terminal-domain has an intact conserved NADPH binding motif (GXSXXG) and the catalytic triad Ser-Tyr-Lys more closely resembles ‘ reducing ’ R-domains than DKC cyclising domains (see ESI † ). 24 Qiao et al predicted a reductive release for ccsA , the PKS-NRPS gene involved in cytochalasin K 4 biosynthesis in Aspergillus clavatus , 27 based on the same rationale, and the co-expression of ccsA with ccsC by Oikawa and co-workers led to the production of the amide 17 , 14 also at the alcohol oxidation state.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments showed high incorporation rates of [methyl‐ 14 C]‐methionine, revealing S ‐adenosyl methionine (SAM) as the methyl group donor for the alkyl branches at the position C‐12 and C‐16 of cytochalasin B, one methylene group at C‐12 and two methyl groups at C‐16 and C‐18 of cytochalasin D . Recent studies demonstrated the molecular basis of biosynthesis of cytochalasin E and K produced by Aspergillus clavatus and have revealed the involvement of a polyketide synthase‐nonribosomal peptide synthetase, in which the biosynthetic pathway could be generalized to other cytochalasins …”
Section: Introductionmentioning
confidence: 99%
“…previously reported undesired oxidative shunting upon expressing key biosynthetic genes involved in cytocholasin K and solanapyrone formation. 30,31 Similar oxidations have been described for the heterologous expression of desmethylbassianin and for the avirulence gene ACE1. 32,33 All observed oxidations occurred at the terminus of linear polyketide precursors such as the observed oxidation of compound 19 to 20.…”
Section: Discussionmentioning
confidence: 81%